2020
DOI: 10.3389/fpsyg.2020.574898
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Labor in Health Care: The Moderating Roles of Personality and the Mediating Role of Sleep on Job Performance and Satisfaction

Abstract: The objective of this study is to investigate the effects of emotional labor on job performance and satisfaction, as well as to examine the mediating effect of sleep problems and the moderating effects of personality traits. A time-lagged study was conducted on 864 health professionals. Scales for emotional labor, sleep, personality traits, and job satisfaction were used and job performance data was obtained from records maintained by human resources. Structural equation modeling was performed to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 80 publications
1
13
0
Order By: Relevance
“…Higher emotional labor among nurses resulted in decreased job satisfaction [ 20 ], presenteeism, perceived organization support (POS) [ 21 ], and professional quality of life [ 16 ], which suggested that emotional labor negatively affects not only the individual but also the organization. POS refers to a set of beliefs that members have about organizational support, which includes such as organizational reward, fairness, favorable job conditions, working environments, closeness with colleagues, and positive atmosphere [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Higher emotional labor among nurses resulted in decreased job satisfaction [ 20 ], presenteeism, perceived organization support (POS) [ 21 ], and professional quality of life [ 16 ], which suggested that emotional labor negatively affects not only the individual but also the organization. POS refers to a set of beliefs that members have about organizational support, which includes such as organizational reward, fairness, favorable job conditions, working environments, closeness with colleagues, and positive atmosphere [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, P3 showed no change in deep acting and P1 showed a decrease in deep acting (from 2 to 1.67), but this decrease was smaller than the decrease in surface acting (from 2.33 to 1). Deep acting, one aspect of emotional labor, requires effort to actually feel and express the required emotions, and some studies show that, unlike surface acting, deep acting is related to better mental health and high job satisfaction [21,22]. Thus, though P2 showed an increase in overall emotional labor level after the mindfulness program, given that deep acting was most affected, it is likely that the mindfulness program still had a positive effect on their mental health and job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…These include different concepts of healthcare quality among different groups of stakeholders. The qualitative component of medical harm policy is crucial, because healthcare services are regarded as involving both affective and emotional labor that is intended to produce an emotional response in patients and, at the same time, require feelings and expression in healthcare workers to fulfil the emotional requirements of the job [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%